PENERAPAN STRATEGI INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN KERAJINAN DI KELAS VII SMP NEGERI 22 PADANG - Nurzela Nurzela; Zubaidah Zubaidah (Serupa The Journal of Art Education, 2020)
The kind of this research is classroomo action research. The subject of this research is student for grade VII-2 SMPN Negeri 22 Padang because this research is motivated by the problems of student learning outcomes. This research is carried out two cycles, one cycle of two meetings. Data were collectedusing teacher observation sheet, student observation sheet, and student learning evaluation.This researchaims to increasing student learning outcomes in craf lessons that using inquiry strategy in SMP Negeri 22Padang.The result of this research in the first cycle is 79,5 increased to 91,75 in the second cycle.Completeness average pre-cycle of student learning outcomes about 56,25% which numbered of 18 people,increased to the first cycle about 84,37% which numbered of 27 people. In the second cycle, all studentcomplete with completeness 100%. Thus, it can be concluded that aplication of inquiry strategy can inprovestudent learning outcomes for grade VII-2 in craf lessons.Keywords : Inquiry Strategy, Student Learning Outcomes.